2016
DOI: 10.1504/ijasm.2016.10002501
|View full text |Cite
|
Sign up to set email alerts
|

Devising a quality management system for new service-support contracts in industry

Abstract: This study proposes a model for a Quality Management System (QMS) for newly awarded service-support contracts. Data collected from service-support projects within the legal and Defence services sectors is analysed and demonstrates that five key constructs are required when devising an effective QMS for a service-support project. It is proposed that from the outset and throughout a project's life, the contractor can continually use key elements identified within the proposed QMS structure to provide the custome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As already indicated above, global companies have adapted their strategy and structure to react to turbulances in the past [15]. Driven by the increasing complexity of products and processes, as well as the ever-increasing dynamism imposed by market and society, companies are increasingly focusing on their core competencies, resulting in much greater flexibility [16]. The additional demand for goods and services as a consequence of outsourcing is covered by a supplier pool.…”
Section: Implementation and Operation Of An Ecosystemmentioning
confidence: 99%
“…As already indicated above, global companies have adapted their strategy and structure to react to turbulances in the past [15]. Driven by the increasing complexity of products and processes, as well as the ever-increasing dynamism imposed by market and society, companies are increasingly focusing on their core competencies, resulting in much greater flexibility [16]. The additional demand for goods and services as a consequence of outsourcing is covered by a supplier pool.…”
Section: Implementation and Operation Of An Ecosystemmentioning
confidence: 99%
“…9 Due to long term commitment, asset owners setup many business processes to govern these asset sustainment activities in order to ascertain good operational outcomes. After analysing three sets of projects, McLay et al 10 found that five key constructs were required to ensure a servicesupport project to be effective in the project life cycle. The five key constructs were: (1) customer and humanistic driven innovation, (2) primary performance drivers, (3) learning from valued resources, (4) focus on quality planning and return on investment, (5) stakeholder collaboration.…”
Section: Introductionmentioning
confidence: 99%